Relational and Organizational Drivers of Job Crafting: Evidence from Jakarta’s Creative Sector - Eva Andayani; Agustian Budi Prasetya; Fakhirani Putri Herrizona (Penerbit Goodwood, 2026)
Purpose: This study aims to examine the effects of Leader-Member Exchange (LMX) and Perceived Organizational Support (POS) on Job Crafting Behaviors (JCB) and to assess the mediating role of Readiness for Change (RFC) among Millennials and Generation Z employees in Jakarta’s creative industry. Research Methodology: A quantitative, cross-sectional design was employed using survey data from 235 employees in Jakarta’s creative sector. Data were collected using a structured questionnaire and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). Results: The findings reveal that POS positively influenced RFC (? = 0.193, p = 0.030) and JCB (? = 0.350, p < 0.001), and LMX positively influenced RFC (? = 0.200, p = 0.036) and JCB (? = 0.307, p = 0.003). However, RFC did not significantly influence JCB (? = 0.066, p = 0.310) and did not mediate the relationships between LMX, POS, and JCB. These findings indicate that job crafting behaviors are more directly driven by relational and organizational support than by employees’ readiness for change. Conclusions: This study extends Social Exchange Theory by showing that reciprocal relationships in dynamic work environments can directly drive proactive behaviors without relying on internal readiness mechanisms. It also provides new insights into job crafting by demonstrating that, within the creative industry, such behaviors are embedded in everyday work practices rather than emerging solely as responses to change. Limitations: The study is limited to selected variables and a specific industry context, indicating the need for future research to incorporate additional individual and contextual factors across sectors. Contributions: Organizations should prioritize strengthening direct relational (LMX) and organizational support (POS) rather than relying on Readiness for Change (RFC) mechanisms to drive job crafting behaviors.